2020
DOI: 10.1186/s13014-020-01613-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring MR regression patterns in rectal cancer during neoadjuvant radiochemotherapy with daily T2- and diffusion-weighted MRI

Abstract: Background: To date, only limited magnetic resonance imaging (MRI) data are available concerning tumor regression during neoadjuvant radiochemotherapy (RCT) of rectal cancer patients, which is a prerequisite for adaptive radiotherapy (RT) concepts. This exploratory study prospectively evaluated daily fractional MRI during neoadjuvant treatment to analyze the predictive value of MR biomarkers for treatment response. Methods: Locally advanced rectal cancer patients were examined with daily MRI during neoadjuvant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Although the survival rate in early stage is high, approximately 80% [ 2 ], loco-regionally advanced stage requires multimodal therapy both pre- and post-surgery in order to improve outcome. The advancement in treatment strategies has been remarkable in the field of rectal cancer, establishing neoadjuvant concurrent chemoradiotherapy (CCRT) as the current standards of care for the locally advanced disease [ 3 , 4 , 5 , 6 , 7 ]. The advances are still in progress and have developed in both ways: treatment intensification, such as total neoadjuvant therapy, and treatment de-intensification, such as the watch-and-wait approach [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the survival rate in early stage is high, approximately 80% [ 2 ], loco-regionally advanced stage requires multimodal therapy both pre- and post-surgery in order to improve outcome. The advancement in treatment strategies has been remarkable in the field of rectal cancer, establishing neoadjuvant concurrent chemoradiotherapy (CCRT) as the current standards of care for the locally advanced disease [ 3 , 4 , 5 , 6 , 7 ]. The advances are still in progress and have developed in both ways: treatment intensification, such as total neoadjuvant therapy, and treatment de-intensification, such as the watch-and-wait approach [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, novel strategies of applying higher RT doses to rectal tumors are emerging as a potential method to allow organ preservation, eliminating surgery in some patients 117 . In addition, recent data have demonstrated that rectal tumors regress during treatment with RT, and this can be seen optimally on MRI 118 . Historically, patients with rectal cancer have been treated with preoperative therapy followed by surgical resection (in some cases, leading to permanent colostomy); however, that paradigm is starting to significantly change.…”
Section: Adaptive Mr Guidance Results In Clinical Practicementioning
confidence: 99%
“…After CRT, the tumor volume is further reduced (l-n), and the T2 value is decreased to 52 ms (o, p) (the patchy red areas on the color-coded image represent fibrosis). The postoperative pathology is classified as TRG 1, with no residual tumor cells found in fibrosis (q, hematoxylin-eosin stain, original magnification ×100) Some prospective exploratory studies reported that MRI during neoadjuvant RCT may predict early pCR in rectal cancer patients [31]. A radiomics model that included MRI values before and during radiotherapy showed excellent predictive capability for identifying pCR in LARC patients, with an AUC of 0.93 [24].…”
Section: Discussionmentioning
confidence: 99%